2015
DOI: 10.3329/jbas.v39i2.25948
|View full text |Cite
|
Sign up to set email alerts
|

Status of Ambient Particulate Matter and Black Carbon Concentrations in Rajshahi Air, Bangladesh

Abstract: Air borne particulate matter (PM) samples (both PM 10 and PM 2.5 ) were collected simultaneously from continuous air quality monitoring station (CAMS) at Rajshahi city from

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…The study area is located in the urban area, and BC is increasing (Begum et al, 2015); thus, it may significantly lead to a rising CH4. Cofala et al (2007) found a similar relationship between BC and CH4 in Asian urban and urban residential areas.…”
Section: Correlations Between Ch4 and Air Pollutantsmentioning
confidence: 99%
“…The study area is located in the urban area, and BC is increasing (Begum et al, 2015); thus, it may significantly lead to a rising CH4. Cofala et al (2007) found a similar relationship between BC and CH4 in Asian urban and urban residential areas.…”
Section: Correlations Between Ch4 and Air Pollutantsmentioning
confidence: 99%
“…From the above discussion, it was observed that although particulate matter has significant impact on human health, very limited work have been conducted upon it. Considering PM, most of the researches focused only in urban background (Hasan et al, 2016;Begum et al, 2015) and traffic areas (Jahida et al, 2014and Begum et al, 2012, 2008 whereas research related to PM focusing on Power Company limited has not been well reported so far. Therefore, this study was carried out to i) observe the PM concentration in midland power company Ltd. at Ashuganj, in Brahmanbaria and to ii) determine BC concentration within the atmospheric PM.…”
Section: Introductionmentioning
confidence: 99%